1998
DOI: 10.1176/ajp.155.10.1339
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Augmentation of Fluoxetine With Clonazepam in the Treatment of Depression: A Double-Blind Study

Abstract: Clonazepam augmentation of fluoxetine was superior to fluoxetine alone in the first 3 weeks of treatment. This strategy may reduce suffering during early SSRI treatment, may partially suppress SSRI side effects, may increase compliance, and could possibly reduce the risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 39 publications
0
42
0
1
Order By: Relevance
“…Conventional antidepressants typically feature a 2-to 6-week delay in response onset, and benzodiazepines have been used for augmentation to reduce the agitation, anxiety, and insomnia associated with depression. Smith et al conducted a double-blind study to determine which was superior for major depression, a combination of clonazepam and fluoxetine or monotherapy with fluoxetine (Smith et al, 1998). Combination therapy of clonazepam and fluoxetine improved major depression significantly more during the first 3 weeks of treatment.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional antidepressants typically feature a 2-to 6-week delay in response onset, and benzodiazepines have been used for augmentation to reduce the agitation, anxiety, and insomnia associated with depression. Smith et al conducted a double-blind study to determine which was superior for major depression, a combination of clonazepam and fluoxetine or monotherapy with fluoxetine (Smith et al, 1998). Combination therapy of clonazepam and fluoxetine improved major depression significantly more during the first 3 weeks of treatment.…”
Section: Indicationsmentioning
confidence: 99%
“…Svestka et al (1995) reported that clonazepam treatment for 3-4 weeks achieved complete remission in 60% of 55 patients with depressive disorder. Smith et al (1998) reported that in an 8-week, double blind study in 80 patients with major depression, the combination of clonazepam and fluoxetine was superior to fluoxetine monotherapy in relieving symptoms of moderate to marked depression, especially during the first 3 weeks. In addition, in 10 days, the combination of clonazepam and fluoxetine achieved the same improvement as obtained with fluoxetine alone by day 56.…”
Section: Optimal Dose and Appropriate Duration Of Treatmentmentioning
confidence: 99%
“…Further, it is reported that SSRIs affect sleep patterns and reduce rapid eye movement (REM) sleep during early phases of treatment, as are reports of increased anxiety and nervousness. [47][48][49][50][51] A number of transcripts show up-and downregulation depending on brain region and/or treatment All three antidepressant treatments induced up-and downregulation of transcripts level. While upregulation was more frequent overall, downregulation was recorded with similar frequency in all brain regions following all three treatments.…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%
“…Adding of a benzodiazepine to an SSRI can provide more rapid symptom relief in depression and more rapid stabilization of panic or social phobia symptoms than the SSRI alone. [20][21][22][23] Benzodiazepines are not recommended as monotherapy in depression, as they primarily improve the symptoms of insomnia and restlessness, rather than the core depressive symptoms of sadness, anhedonia, and low energy. 24 In our study the mean age was 36 years, majority of participants were between 26-35 years, indicating a peak occurrence in 2 nd and 3 rd decades of life.…”
Section: Discussionmentioning
confidence: 99%